Effectiveness of management zones for recovering parrotfish species within the largest coastal marine protected area in Brazil - Pedro H. C. Pereira; Julia Caon Araujo; Gislaine V. Lima; Luís G. F. Côrtes; Erandy Gomes; Rafael A. Magris (Scientific Reports, 2022)
Abstract The establishment of multiple zones offering different protection levels within a Marine Protected Area (MPA) can minimize social conflicts while maintaining associated biodiversity benefits such as fish population replenishment. Parrotfishes are among one of the most ecologically important reef fishes; yet extremely overexploited worldwide. In this context, well-designed priority management areas allowing no fishing activity (no-take zones) could help recover fish species, such as parrotfishes, through a MPA zoning process. Here, we tested this hypothesis by identifying the spatial configuration of zones that maximize the recovery of endangered parrotfish species (Scarus trispinosus; Scarus zelindae; Sparisoma amplum; Sparisoma axillare; Sparisoma frondosum) at the largest MPA in Brazil protecting nearshore coral reefs (MPA Costa dos Corais). We used parrotfish distribution data to produce species distribution models (SDMs) and combined them with conservation planning tools to delineate priority zones following a systematic approach. Then, we contrasted priority zones against non-systematic, newly designed no-take zones based on managers’ and stakeholders’ perspectives. After mapping the predicted abundance of each species within both zones based upon field surveys, we found that priority zones were more effective than non-systematic ones for the protection of two out of the five species: Scarus trispinosus and Sparisoma amplum. Thus, we considered that designing systematic zones was particularly relevant for increased protection of the two parrotfish species facing the largest decline. The prioritization analyses also showed that priority areas for parrotfish conservation following a systematic approach were mostly located surrounding and within no-take zones delineated by local stakeholders. The spatial overlap between systematic and non-systematic zones was of 38%. Hence, our study reinforces the importance of considering scientific information and methods (e.g., spatial distribution data and prioritization analyses) as a complementary strategy along with local stakeholders’ knowledge, for delineating and refining management zones within MPAs.